Adrian van Kaam's formation science and formative spirituality: Some implications for religious education (with special reference to the Philippines and other areas of Asia) - Garvey, William, FSC (Animo Repository, 1989)
This dissertation is one of the first times that presents the need to Philippine and Asian academe, the basic thinking of Adrian van Kaam and the Institute of Formative Spirituality of Duquesne University of Pittsburgh, Pennsylvania the need to apply aspects of this thinking to aspects of Philippine and Asian realities and life and the need to apply this thinking especially to the field of religious education. The conclusions of the study are stated, as follows: The study accepts the excellence of formation science/formative spirituality as taught by the Institute of Formative Spirituality. It is very appreciative of the varied and creative implications that formation science/formative spirituality have in the areas of reading, prayer, liturgy, personality development, spiritual direction, ministry, and social justice and how such implications can be seen in various ways both in the Philippines and other areas of Asia. Also, the study accepts a possible threefold division of twentieth century writings on education to normal human growth: religious education, Christian education, and catechesis. The dissertation further concludes that formation science/formative spirituality is applicable in each and all of these three categories of education, and that it has many and varied implications for these three educational categories (and with some special applications to these three categories in the Philippines and other areas of Asia depending on religious faith traditions).